MNE internationalization patterns, the roles of knowledge stocks, and the portfolio of MNE subsidiaries - Hutzschenreuter, Thomas; Matt, Tanja (Journal of International Business Studies, 2017)
Learning and knowledge are crucial to the internationalization process of the firm. Johanson and Vahlne (1977, 2009) put gaining experience, i.e., learning and accumulating knowledge at the heart of their internationalization model. We posit that the IB field has perhaps moved too fast from conceptual work to quantitative empirical studies, not devoting sufficient attention to the idea of experiential learning, either conceptually or empirically. We look at the most cited internationalization studies to assess their theoretical and empirical contributions to experiential learning and knowledge stock accumulation and to the important role played by the portfolio of MNE subsidiaries as a knowledge source. We extend theory by carefully laying out how a growing portfolio of subsidiaries leads to accumulation of particular kinds of knowledge stocks, which can help with subsequent expansion moves. We show also how the concept of added distance supports this argumentation, thereby contributing to the theoretical and empirical work on the “further internationalizing” MNE.